(untitled) (Marketing Journal, 2025)
This study investigates the relationship between e-commerce variables and GDP growth in developing countries using panel data estimation techniques. The analysis employs a regression model that includes key determinants such as e-commerce market growth, revenue from e-commerce, secure internet servers, the UNCTAD B2C E- commerce Index, the percentage of internet shoppers, and the share of individuals using the internet. By utilizing balanced panel data from 20 developing countries, this research aims to uncover the dynamic effects of e-commerce on economic growth. The results suggest significant relationships among the variables, highlighting the importance of e-commerce development for stimulating GDP growth in these economies.